Polymorphism of genes and drug-induced liver injury - P. Ye. Tkachenko; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze publications in the world scientific literature on relation between druginduced liver injury and genetic polymorphism of enzymes and transport systems, xenobiotics involved in metabolism.Key points. Drug-induced liver injury can be accompanied by wide spectrum of clinical symptoms, ranging from asymptomatic elevation of aminotransaminases activity to development of fulminant liver failure. The most cases are related to idiosyncrasy phenomenon which is based on genetic predisposition for production of reactive metabolites at xenobiotic transformation reactions in the liver. Types of genetic polymorphism known for today to be associated with the risk of druginduced liver injury are presented in this article. The perspective trends in diagnostics based on application of molecular genetic methods are taken into account as well.Conclusion. Studies of genetic polymorphism of enzymes and transporters involved in xenobiotic metabolism in the liver, looks to be perspective. Data of investigations allow to expand the concept of pathogenetic mechanisms of drug-induced liver disease, that, in turn, promotes development of the test systems providing diagnostics at molecular genetic level.